COMMUNITY EMPOWERMENT THROUGH BROWN SUGAR HOME INDUSTRY BY VILLAGE COMMUNITY EMPOWERMENT INSTITUTIONS IN KUBANGGEDE BLOCK AREA, CIKULU HAMLET, SUKAHURIP VILLAGE, SUB-DISTRICT OF PANGANDARAN: Array - Sophiatun Wahidah; Kiki Endah; Agus Nurulsyam Suparman; Fachmi Syam Arifin (Faculty of Social And Political Science Universitas Galuh, 2021)
The background of this research, namely community empowerment through the Brown Sugar Home Industry by the Sukahurip Village Community Empowerment Institute is still low. According to preliminary observations, the writer found various problems in the field such as: 1) Village Community Empowerment Institutions have not yet provided new ideas to the brown sugar home industry community. 2) Low training and guidance for the brown sugar home industry community by the Village Community Empowerment Institution. 3) Low funding assistance from LPMD for the brown sugar home industry community. Methodology of this research is used qualitative research methods using a descriptive qualitative approach. Based on the results of the research, it is known that Community Empowerment through the brown sugar home industry by the Village Community Empowerment Institute in the Kubanggede Block Area, Cikulu Hamlet, Sukahurip Village, District of Pangandaran has not been implemented properly. Where the empowerment carried out by the Sukahurip Village Community Empowerment Institute has not been implemented optimally. Evidenced by the table recapitulation of research results with 27 questions indicating that there are indicators that have not been implemented properly. The obstacles in the implementation of empowerment are the absence of financial assistance, the absence of new ideas provided by the LPMD, the absence of training and coaching from the LPMD, the absence of marketing of brown sugar products from the LPMD. The fforts that made are helping with the contribution of funds from the Village Government, optimizing training and coaching, helping to improve the capacity of the community with new ideas provided by LPMD.